Barbár vádlottak – gondolatok Móricz Zsigmond Barbárok c. novellája nyomán - Fejesné Varga, Zita (Debreceni Jogi Műhely, 2016)
Zsigmond Móricz's works from the 1930s present areas barely affected by civilization; his short stories titled 'Barbarians' were published in 1932.The short story 'Barbarian' is about 2 shepherds - in the rigid world of shepherds living away from civilization - killing shepherd Bodri, his little son and his 3 shepherd dogs, just for the benefit of taking Bodri's 300 sheeps. The short story 'Barbarians' displays the confrontation of the good and the bad, with the moral content that sin never goes unpunished - be it moral contempt, social exclusion, public contempt, gnawing guilt, or even the judgement of a criminal court.Móricz does not exactly describe the age when his story takes place, but it may be inferred.The shortstory is made up of 3 chapters. From a legal perspective the short story can be considered a judicial decision, which is made up of statements of facts, evidence evaluation and decision. From a procedural perspective the investigation process and the trial phase can be separated. Criminal law and criminal procedural elements in effect at the time of writing the story and presently are well recognizable.In the story the statutory definition of two crimes can be observed: murder and cruelty to animals. The motives of the homicide as well as aggravating circumstances are clear: pre-arranged, crime against property, to the detriment of several people, repeat offender, offence against a person under fourteen years of age.The end of the story takes us to the idea that the word communicated by the judge: "barbarians", can be considered as a real punishment in itself for the defendants, followed by death by hanging. The judgment is therefore twofold: punishment according to the law, as well as by human society.